Interpersonal relationship in nursing: considerations on the education/practice of vocational nurses - Ribeiro, Maria Inês Lemos Coelho (2001)
This is a reflection concerning interpersonal relationships in nursing programs and in the professional practice of nursing auxiliaries and nursing aides. It is verified that patients' requests are found in the relational sphere and rarely in the technical one. Interpersonal relationships appear as the driving incentive of health care. It is known that 70% of nursing labor is developed by vocational nursing professionals who perform a large number of procedures, which justifies this study. That the mentioned professionals should have a better preparation concerning the theme in question in order to provide more humanized care was considered to be essential. Vocational Nursing schools are obliged to provide the necessary conditions for the development of such skill and the clinical nurse is responsible for keeping it, especially by means of continual educational activities at work.